Excerpts and memories from the periods of border security in Hungary (Belügyi Szemle, 2025)
Aim: The purpose of this study is to enhance understanding of the evolution of the Hungarian Border Guard, by providing an overview of the various historical events and forces that shaped the organization throughout different periods.Methodology: By drawing on a broad literature covering various periods in the history of border surveillance in Hungary, this study provides a detailed examination of the history of the Hungarian Border Guard.Findings: It is imperative to work to preserve the memory and traditions of the Border Guard, as this is the only path to maintaining its spirit into the future.Value: This study provides the reader with an understanding of the history, spirit, and messages of the Hungarian Border Guard. A great deal of recent work has been conducted to preserve these memories. Several significant monuments have been created, including the Apátistvánfalva Border Guard Memorial Site, established in the former Apátistvánfalva border guard post, and the Border Guard Memorial Room at the Border Guard Department of the National University of Public Service, Faculty of Law Enforcement. The dedication of those working to protect these traditions is exemplary; the significance of their work is unquestionable. The protection of the values ​​of the Border Guard and the preservation of its traditions is arguably a matter of public interest.